The Macroeconomic Impact On Investment Decisions in manufacturing companies Listed on the Indonesia Stock Exchange (BEI) - Karma Karma; Rahmayati Rahmayati; Seniorita Seniorita (Cita konsultindo, 2023)
The aim of this research is twofold: 1) to examine and analyze how interest rates, inflation, and exchange rates impact investment decisions, and 2) to explore how interest rates, inflation, exchange rates, and investment decisions affect the value of manufacturing companies listed on the Indonesia Stock Exchange.This study adopted a causal approach using secondary data gathered from financial statements of manufacturing companies listed on the Indonesia Stock Exchange, obtained from various sources including the Indonesian Capital Market Directory (ICMD) data via the Capital Market Information Center (PIPM) Makassar office, the Indonesia Stock Exchange website, the Bank of Indonesia website, and the Badan Pusat Statistic (BPS) website. The population of this study consisted of all manufacturing companies listed on the Indonesian stock market. The sampling technique used was purposive sampling, which resulted in 45 companies being selected, each with financial statements covering a 5-year period, thereby providing a total of 225 observations. The method of analysis used in this study was path analysis. The findings revealed that interest rates and inflation have a negative impact on investment decisions, while exchange rates have a positive impact.